2013
DOI: 10.1603/me13049
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Mosquitoes (Diptera: Culicidae) From Florida to Transmit Rift Valley Fever Virus

Abstract: We evaluated Aedes atlanticus Dyar and Knab, Aedes infirmatus Dyar and Knab, Aedes vexans (Meigen), Anopheles crucians Wiedemann, Coquillettidia perturbans (Walker), Culex nigripalpus Theobald, Mansonia dyari Belkin, Heinemann, and Page, and Psorophora ferox (Von Humboldt) from Florida to determine which of these species should be targeted for control should Rift Valley fever virus (RVFV) be detected in North America. Female mosquitoes that had fed on adult hamsters inoculated with RVFV were incubated for 7-21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 46 publications
2
56
0
Order By: Relevance
“…Eight experimental studies were identified that fit the inclusion criteria for this analysis [21], [29][35]. Data for 26 mosquito species were adjusted utilizing the viremic dose-dependent relationship of dissemination and transmission rates based on 17 species of mosquitoes (Figure S1, A and B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eight experimental studies were identified that fit the inclusion criteria for this analysis [21], [29][35]. Data for 26 mosquito species were adjusted utilizing the viremic dose-dependent relationship of dissemination and transmission rates based on 17 species of mosquitoes (Figure S1, A and B).…”
Section: Resultsmentioning
confidence: 99%
“…Selected studies evaluated mosquito species that occur in the U.S. and monitored dissemination and transmission rates after feeding on a RVFV infected animal at the incubation temperature of 26°C. RVFV vector competence studies were located using Web of Science, NCBI's Pubmed, and the Armed Forces Pest Management Board Literature Retrieval Systems [21], [29][35].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports have indicated that RVFV has been isolated in from over 30 mosquito species [5] of mosquito. As these mosquitoes are distributed around the world, RVFV is prone to spread to Europe, America, and other non-epidemic areas [5,[8][9][10]. Indeed, with the development of international trade in animal and animal products, population migration, and climate change, the risk of RVFV spreading increases continually.…”
Section: Introductionmentioning
confidence: 99%